2012
DOI: 10.1210/me.2011-1162
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine Methyltransferase 5 (Prmt5) Promotes Gene Expression of Peroxisome Proliferator-Activated Receptor γ2 (PPARγ2) and Its Target Genes during Adipogenesis

Abstract: Regulation of adipose tissue formation by adipogenic-regulatory proteins has long been a topic of interest given the ever-increasing health concerns of obesity and type 2 diabetes in the general population. Differentiation of precursor cells into adipocytes involves a complex network of cofactors that facilitate the functions of transcriptional regulators from the CCATT/enhancer binding protein, and the peroxisome proliferator-activated receptor (PPAR) families. Many of these cofactors are enzymes that modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 95 publications
4
61
0
Order By: Relevance
“…For example, SWI/SNF chromatin remodelling enzymes are required for the differentiation of most tissue types (57,58) yet are reported to act as negative regulators of transcription at specific stages of some tissue differentiation events (59) and during ES cell differentiation (60–62). The arginine methyltransferase Prmt5, like Safb1, was initially characterized as a negative regulator of gene expression yet was subsequently shown to be required for both myogenic- and adipogenic-specific gene expression and differentiation (28,63,64). The functional activity of each of these regulators is likely the same regardless of context; positive or negative outcomes with regard to transcriptional regulation are almost certainly dependent on the local chromatin environment in which the regulator functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SWI/SNF chromatin remodelling enzymes are required for the differentiation of most tissue types (57,58) yet are reported to act as negative regulators of transcription at specific stages of some tissue differentiation events (59) and during ES cell differentiation (60–62). The arginine methyltransferase Prmt5, like Safb1, was initially characterized as a negative regulator of gene expression yet was subsequently shown to be required for both myogenic- and adipogenic-specific gene expression and differentiation (28,63,64). The functional activity of each of these regulators is likely the same regardless of context; positive or negative outcomes with regard to transcriptional regulation are almost certainly dependent on the local chromatin environment in which the regulator functions.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the DNA methylome of mature adipocytes develops early in the lineage differentiation, and that the large majority of adipocyte genes is 'ready' for transcriptional induction as early as the preadipocyte stage. The limiting and necessary factor is PPARγ2, whose expression and DNA binding activity are controlled by epigenetic mechanisms during adipogenesis (Fujiki et al, 2009;LeBlanc et al, 2012;Wang et al, 2013a,b). Interestingly, the expression of PPARγ2 was reduced in the adipose tissue of diabetic mice, and this was due to repressive methylation of its promoter region (Fujiki et al, 2009), indicating that DNA methylation of PPARγ2 is important for adipose tissue (dys)function.…”
Section: Adipogenesismentioning
confidence: 99%
“…Specific interaction of PRMT5 with cooperator of PRMT5 (Co-Pr5) is required for PRMT5 nuclear functions especially in symmetric arginine dimethylation on histone H4 (H4R3me2s) [5]. Prmt5 deletion is embryonic lethal in mouse and is required for proliferation and/or differentiation of several stem cell lineages including ES cells [6], skeletal muscle stem cells [79], adipose stem cells [10], hematopoietic stem and progenitors [11], chondrocyte progenitors [12] among others. PRMT5 is also required for important cellular processes such as maintenance of chromatin states [13], cell cycle and RNA splicing [14].…”
Section: Introductionmentioning
confidence: 99%